PENGARUH FINANCIAL LITERACY, DIGITAL MARKETING DAN WORD OF MOUTH TERHADAP MINAT MENGGUNAKAN INTERNET BANKING PADA NASABAH PT BANK NEGARA INDONESIA (PERSERO) TBK. KC PONOROGO SELAMA PANDEMI COVID-19 - Fahmi Maulana Rahmatulloh; Ahadiati Rohmatiah; Hartirini Warnaningtyas (Universitas Merdeka Madiun, 2022)
he Covid-19 pandemic in various countries around the world, including Indonesia, has encouraged an increase in financial and banking transactions carried out by the public through internet banking services. This study aims to determine the effect of Financial literacy, digital marketing and word of mouth on the interest in using internet banking for customers of PT Bank Negara Indonesia (Persero) Tbk. KC Ponorogo during the Covid-19 pandemic. Population in this study were customers of PT Bank Negara Indonesia (Persero) Tbk. KC Ponorogo from November 2020 to November 2021, totaling 1552 customers. The research sample amounted to 100 people whose size was determined by the Slovins formula. Sampling using purposive sampling technique. The research instrument used a questionnaire. The data analysis technique used the Partial Least Square (PLS) method with SmartPLS version 3.0 software. The results showed that; 1) Hypothesis 1 was rejected. This means that Financial literacy had no significant effect on customers' interest in using internet banking during the Covid-19 pandemic. 2) Hypothesis 2 was accepted. This means that digital marketing had a significant effect on customers' interest in using internet banking during the Covid-19 pandemic. 3) Hypothesis 3 was accepted. This means that word of mouth had a significant effect on the interest in using internet banking for customers of PT Bank Negara Indonesia (Persero) Tbk. KC Ponorogo during the Covid-19 pandemic.